The musicscape in hotel businesses: Evidence from online reviews - Çatir, Ozan (Turyzm/Tourism, 2023)
Musicscape is an important topic in tourism and hospitality contexts. However, there are few studies on this subject in the accommodation sector. The study aims to determine the effect of ‘musicscape dimensions’ on customer behavior. To achieve this aim, 2357 online reviews of 28 hotels in Antalya, Turkey were analyzed by content analysis. The framework proposed by Oakes was used in the study. The research findings provide hotel managers with practical advice on the effective use of musicscape in tourism and hospitality settings. In addition, it was concluded that customers evaluated the loudness and fast tempo of music negatively, and that the harmony of music broadcasts and their environment offered by a hotel is positively perceived by customers.